2020
DOI: 10.3390/toxins12080527
|View full text |Cite
|
Sign up to set email alerts
|

Seaweed Essential Oils as a New Source of Bioactive Compounds for Cyanobacteria Growth Control: Innovative Ecological Biocontrol Approach

Abstract: The application of natural compounds extracted from seaweeds is a promising eco-friendly alternative solution for harmful algae control in aquatic ecosystems. In the present study, the anti-cyanobacterial activity of three Moroccan marine macroalgae essential oils (EOs) was tested and evaluated on unicellular Microcystis aeruginosa cyanobacterium. Additionally, the possible anti-cyanobacterial response mechanisms were investigated by analyzing the antioxidant enzyme activities of M. aeruginosa cells. The resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 71 publications
2
13
0
Order By: Relevance
“…In comparison to the May samples, there was a more than two-fold lower amount detected in the August samples. This compound was also previously reported as an abundant fatty acid in different Cystoseira species [3,4,8,14,21,22]. The May extract also contained the highest share of eicosanoic acid (2.58%).…”
Section: Resultssupporting
confidence: 72%
See 3 more Smart Citations
“…In comparison to the May samples, there was a more than two-fold lower amount detected in the August samples. This compound was also previously reported as an abundant fatty acid in different Cystoseira species [3,4,8,14,21,22]. The May extract also contained the highest share of eicosanoic acid (2.58%).…”
Section: Resultssupporting
confidence: 72%
“…This compound was detected in the lowest concentration in the June sample (2.9%), but in the next two months its content was almost 2 and 5-fold greater. El Amrani Zerrifi et al [21] confirmed the domination of phytol in C. tamariscifolia from their study, as well as Bouzidi et al [13] in C. sedoides. Other dominant components from the chemical class of alcohols were oleyl alcohol and n-nonadecan-1-ol, for which the regular amount increase during the collecting months was recorded.…”
Section: Resultssupporting
confidence: 61%
See 2 more Smart Citations
“…From another angle, El Amrani Zerrifi et al [13] investigated the potential of employing natural compounds extracted from seaweeds to control harmful algae in aquatic ecosystems. The authors report the results of a series of anti-cyanobacterial assays with different extracts from seaweeds from Morocco, which demonstrate the anti-cyanobacterial properties of Cystoseira tamariscifolia and its potential use in developing environmentally friendly procedures to control the growth of toxic cyanobacteria.…”
mentioning
confidence: 99%